(untitled) (Annals of Medical Research, 2021)
Aim: Lumbar microdiscectomy (LMD) is considered as a gold standard surgical technique for the treatment of patients with lumbar disc hernia (LDH) although various types of treatment are being developed. This study aimed to investigate the safety and efficacy of LMD in our clinic.Material and Methods: The study exclusively included 271 patients undergoing LMD due to LDH. Preoperative and postoperative (10th day, 1st month, and long-term) Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) scores of the patients were compared. Clinical outcomes were analyzed retrospectively based on modified Macnab criteria. Complications were noted. SPSS Statistics 22.0 software package was used to analyse the data for pre- and postoperative VAS and ODI scores. A p value of 0.05 was considered statistically significant.Results: The mean length of stay in the operating room and hospital was 165.04±36.99 min and 1642.02±574.90 min, respectively. There was a significant decrease in postoperative VAS and ODI (%) scores compared to preoperative scores. Preoperative VAS and postoperative long-term VAS scores were 8.99±0.62 and 1.38±0.95, respectively whereas preoperative ODI (%) and postoperative long-term ODI (%) scores were 85.33±6.74 and 12.96±9.58, respectively (p0.001). The success rate for excellent or good outcomes according to the modified Macnab criteria was 87.45%. During surgery, cerebrospinal fluid (CSF) leak and dura defect developed in four patients (1.48%) and there was only dura defect in two patients (0.73%). After the surgery, recurrent LDH, spinal infection, and spinal epidural hematoma developed in seven (2.58%), three (1.11%), and one patient (0.37%), respectively.Conclusion: LMD is an effective and safe method in the treatment of LDH as it has low complication rates and high success rates.